2002
DOI: 10.1016/s0022-3999(01)00228-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and psychological distress in the working population

Abstract: Objective: The purposes of this study were: (1) to explore the relationship between fatigue and psychological distress in the working population; (2) to examine associations with demographic and health factors; and (3) to determine the prevalence of fatigue and psychological distress. Methods: Data were taken from 12,095 employees. Fatigue was measured with the Checklist Individual Strength, and the General Health Questionnaire (GHQ) was used to measure psychological distress. Results: Fatigue was fairly well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
10
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(207 citation statements)
references
References 20 publications
(34 reference statements)
9
185
10
3
Order By: Relevance
“…Due to better health status it may be easier to perform selfmanagement activities, which may result in less diabetes symptoms. In addition to the inability to draw causal conclusions, the results of this study may be limited due to the relatively high non-response, although the response rate is comparable to those found in other studies on related topics [39,40]. Therefore, we assume that generalizability of results will not be more problematic here than in other studies.…”
Section: Discussionmentioning
confidence: 62%
“…Due to better health status it may be easier to perform selfmanagement activities, which may result in less diabetes symptoms. In addition to the inability to draw causal conclusions, the results of this study may be limited due to the relatively high non-response, although the response rate is comparable to those found in other studies on related topics [39,40]. Therefore, we assume that generalizability of results will not be more problematic here than in other studies.…”
Section: Discussionmentioning
confidence: 62%
“…Using this cut-off point, workers with a total CIS score higher than 76 for total CIS score are considered as probable fatigue cases, with a fatigue level that can be indicated as putting the employee at risk for sick leave or work disability. Bultmann et al showed that the prevalence of fatigue in the working population is 21.9% 29) . According to the cutoff scores of BDI-II, Kojima et al reported that 80.7% of the participants scored in the minimal range (0-13) for depression in the working population 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged fatigue is associated with impairments comparable to chronic medical conditions, and may affect the individual's performance and functioning in the occupational as well as home setting (BÜLTMANN et al 2002;BÜLTMANN et al 2003;JONG et al 2003;HULST et al 2006;JANSSEN et al 2003). Mental fatigue is defi ned and operationalised in various ways, for example in terms of increased sleepiness, reduced alertness, reduction in motivation, reduction in activity, and reduction in concentration (JANSSEN et al 2003;TARIS et al 2006).…”
Section: Mental Fatiguementioning
confidence: 99%